Needs Analysis for the Development of a Problem-Based Learning Model Based on Deep Learning for the Topic of Faith (Iman) and Piety (Taqwa) in Elementary School Students - Imam Taufiq HA; Umi Chotimah; Erna Retna Safitri (Journal of Educational Sciences, 2026)
This study aims to analyze students’ needs in moral (akhlaq) learning as a foundation for developing more contextual and relevant learning models and media. The research employed a descriptive quantitative approach using a needs-analysis questionnaire administered to elementary school students. The results indicate that the Learning Experience aspect obtained an average score of 85.54%, categorized as very high, showing that students generally experience moral learning positively and are actively engaged in the classroom. In contrast, the Difficulties and Challenges aspect obtained an average score of 35.62%, categorized as moderate, indicating that students still encounter difficulties in understanding abstract moral concepts and relating them to real-life situations. Meanwhile, the Need for New Learning Models and Media aspect reached 85.76%, also in the very high category, reflecting students’ strong expectations for more interactive, contextual, and technology-supported learning environments. These findings reveal a gap between students’ positive learning experiences and the limitations of existing instructional approaches. Therefore, the results provide a strong empirical foundation for developing a Problem-Based Learning (PBL) model supported by digital or AI-based learning media to enhance engagement, contextual understanding, and the internalization of moral values among elementary school students.